Sifilis Sekunder Koinfeksi HIV dan Tuberkulosis Paru Alergi terhadap Penicillin: Laporan Kasus - Laura Nanda Prameswari; Nadya Wulandari Alshanti; Ayik Rochyatul Jannah (PT Kalbe Farma Tbk., 2025)
Background: Syphilis infection could occur simultaneously with other diseases such as TB and HIV. Case: A 24-year-old male with red spots on his hands, body, and feet for 2 weeks without pain, itching, nor burning sensation. Physical examination revealed multiple erythematous polymorphic scaly macules with clear borders, size 0.5-1 cm, accompanied by scuama. VDRL titer 1:16, and TPHA titer 1:320. The patient was also tested positive for HIV and TB. The patient was allergic to benzathine penicillin G, so the patient was given alternative syphilis therapy doxycycline 2x100 mg for 14 days. He was clinically improved and VDRL titers decreased. Conclusion: Screening for other infectious diseases such as HIV and TB is necessary in syphilis cases due to the high incidence of co-infection with other diseases.